Ciencia e investigación agraria 2019
DOI: 10.7764/rcia.v46i2.2098
|View full text |Cite
|
Sign up to set email alerts
|

Quinoa leaf as a nutritional alternative

Abstract: A. Vazquez-Luna, V. Pimentel Cortés, F. Fuentes Carmona, R. Díaz-Sobac. 2019. Quinoa leaf as a nutritional alternative. Cien. Inv. Agr. 46(2): 137-143. Chenopodium quinoa is an herbaceous plant that possesses green polymorphic leaves. They are traditionally consumed in America and are considered nutritive vegetables. Most vegetables are considered valuable sources of micronutrients, such as mineral, vitamins, carbohydrates and dietetic fiber; however, because they are poor in proteins, they are considered to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Their nutritional profile surpasses the grain, and they possess interesting potential in nutrition and food. Quinoa leaves can be used in the preparation of salads, soups, main dishes, and as raw material to enter the food industry, which wants to offer a continuous movement of new products in order to remain in the market, thereby contributing to the change of the production matrix [ 76 , 77 ].…”
Section: Quinoa Processing and Agroindustrymentioning
confidence: 99%
“…Their nutritional profile surpasses the grain, and they possess interesting potential in nutrition and food. Quinoa leaves can be used in the preparation of salads, soups, main dishes, and as raw material to enter the food industry, which wants to offer a continuous movement of new products in order to remain in the market, thereby contributing to the change of the production matrix [ 76 , 77 ].…”
Section: Quinoa Processing and Agroindustrymentioning
confidence: 99%
“…The green leaves and tender stalks have high nutritional value and can be consumed raw or cooked, similar to, for instance, spinach [29,30]. Several studies have reported that the PC in quinoa leaves is greater than in quinoa grains, reaching over 25-37% in the DM, compared to 9.1-15.7% in grains [29,31,32]. The proximate composition of quinoa leaves’ crude fat, crude fiber, carbohydrates and energy is 2.4- 4.5%, 6.9-7.8%, 34% and 325 Kcal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…La quinua posee hojas que son igual de ricas en valores nutricionales y compuestos bioactivos. Se consumen tradicionalmente en América y se consideran vegetales nutritivos (Vazquez-Luna, 2019). Además, hay informes donde indican la idoneidad del uso potencial de la planta joven de quinua como un nuevo cultivo de verduras de hoja no tradicional, por presentar características nutricionales potenciales (Abd et al, 2018).…”
Section: Introductionunclassified